Desenvolvimento e comparação de células solares bifaciais industriais com deposição de dopante com boro por spin-on - Costa, Rita de Cássia da (2013)
The aim of this thesis was the development of industrial bifacial solar cell on ntype FZ-Si and Cz-Si wafers, metallized by screen printing. The boron diffusion was performed with the dopant PBF-20. The sequence of the dopant (B and P) diffusion was assessed and in a process the oxidation was done at the same thermal step of boron diffusion. Bifacial solar cells were developed in FZ-Si wafers using the process with phosphorus diffusion before the boron diffusion. The best solar cell was processed with boron diffusion at 1000° C during 20 minutes and achieved 14.3% (emitter) and 13.7% (back surface field) efficiencies. With boron diffusion before the phosphorus diffusion and oxidation in the same step that the boron diffusion, the best solar cell was developed with the oxidation of 30 minutes. The firing process of metal pastes was performed at 860 °C and belt speed of 240 cm/min. The best bifacial solar cell reached 13.5% (face with phosphorus) and 11.8% (side with boron) efficiencies. The fill factor of 0.61 (emitter) limited the efficiency. Bifacial solar cells were developed on Cz-Si wafers, with boron diffusion before the phosphorus diffusion. The best efficiency was achieved with oxidation of 40 minutes. The increase of oxygen flow produced solar cells with greater uniformity of efficiency. However, when the solar cells were processed in the presence of nitrogen, the efficiency was reduced mainly in the emitter. The firing temperature of the best solar cell was 840 °C and the belt speed was 200 cm/min. The efficiency was of approximately 13.3 % in both faces. When illuminated by the emitter, the solar cells developed in both kinds of substrate showed similar efficiency of 13.3 % -13.5 %. In the back surface filed, the efficiency of solar cells processed in FZ-Si was limited by fill factor.